2018
DOI: 10.3389/fnmol.2018.00002
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Alterations in Neurodegenerative Diseases and Their Relation to Abnormal Energy Metabolism

Abstract: Neurodegenerative diseases (NDDs) are disorders characterized by progressive deterioration of brain structure and function. Selective neuronal populations are affected leading to symptoms which are prominently motor in amyotrophic lateral sclerosis (ALS) or Huntington’s disease (HD), or cognitive in Alzheimer’s disease (AD) and fronto-temporal dementia (FTD). Besides the common existence of neuronal loss, NDDs are also associated with metabolic changes such as weight gain, weight loss, loss of fat mass, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 177 publications
2
86
0
2
Order By: Relevance
“…Of relevance, hypothalamic atrophy was identified in ALS in both symptomatic and presymptomatic cohorts and correlated with body mass index 8 9. Similar findings have been identified in frontotemporal dementia10 11 and suggest that changes in neural pathways and central factors may have a pivotal role in controlling food intake and energy metabolism,12 either as pathogenic drivers or as adaptive mechanisms. Disentangling pathogenic pathways from compensatory responses will be challenging in future studies as it seems likely that the body tries to adapt to the imbalance of increased energy metabolism by rewiring hypothalamic neural circuits leading to increased food intake 13.…”
Section: Hypermetabolism May Be Linked To Neurodegenerative Processessupporting
confidence: 75%
“…Of relevance, hypothalamic atrophy was identified in ALS in both symptomatic and presymptomatic cohorts and correlated with body mass index 8 9. Similar findings have been identified in frontotemporal dementia10 11 and suggest that changes in neural pathways and central factors may have a pivotal role in controlling food intake and energy metabolism,12 either as pathogenic drivers or as adaptive mechanisms. Disentangling pathogenic pathways from compensatory responses will be challenging in future studies as it seems likely that the body tries to adapt to the imbalance of increased energy metabolism by rewiring hypothalamic neural circuits leading to increased food intake 13.…”
Section: Hypermetabolism May Be Linked To Neurodegenerative Processessupporting
confidence: 75%
“…The spatiotemporal progression of NFTs from the entorhinal cortex and the hippocampus to the isocortical areas has been shown to be correlated with cognitive deficits [85], supporting a pivotal role for Tau pathology and spreading in AD-related memory impairments [86]. Interestingly, hypothalamus that plays a key role in the central control of energy metabolism has been also shown to display alterations in AD [87, 88]. In a study investigating 28 patients with AD, 22 patients showed plaques and NFTs in the hypothalamus [87].…”
Section: Overview On Tau and Tauopathiesmentioning
confidence: 99%
“…stein and Amir, 1999). Hypothalamic regions are also good candidates as alterations have been reported both in HD patients and animal models (Vercruysse et al, 2018;Cheong et al, 2019). The dorsomedial hypothalamic nucleus is responsible for relaying circadian temporal information from the SCN to the locus ceruleus (Gompf and Aston-Jones, 2008), and excitotoxic lesion of this region has been reported to decrease behavioral circadian rhythms including locomotor activity (Chou et al, 2003).…”
Section: Discussionmentioning
confidence: 99%